2012
DOI: 10.1038/ni.2342
|View full text |Cite
|
Sign up to set email alerts
|

TCR clonotypes modulate the protective effect of HLA class I molecules in HIV-1 infection

Abstract: Human leukocyte antigen (HLA) B*27 and B*57 are associated with protection against HIV-1 disease progression, yet most persons expressing these alleles are unable to control HIV-1. Here we show that HLA-B*27-restricted CD8+ T cells in controllers and progressors differ in their ability to inhibit virus replication through targeting of the immunodominant Gag epitope. This is associated with distinct TCR clonotypes, characterized by superior control of HIV-1 replication in vitro, greater cross-reactivity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
218
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(240 citation statements)
references
References 50 publications
(89 reference statements)
19
218
3
Order By: Relevance
“…Furthermore, special thymic selection inducing a larger B27-driven CD8 1 T cell precursor repertoire, preferential usage of certain T cell receptor (TCR) clonotypes associated with higher cross-reactive and, finally, better capacity of evasion from regulatory T cell (T reg )-mediated suppression have also been documented [55][56][57][58].…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%
“…Furthermore, special thymic selection inducing a larger B27-driven CD8 1 T cell precursor repertoire, preferential usage of certain T cell receptor (TCR) clonotypes associated with higher cross-reactive and, finally, better capacity of evasion from regulatory T cell (T reg )-mediated suppression have also been documented [55][56][57][58].…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%
“…In addition, both central memory (19) and effector memory (20,21) phenotypes have been associated with viremic control, particularly in the absence of negative regulation (22)(23)(24)(25). More recently, the clonotypic composition of HIV-specific CD8 T cell populations has also emerged as a key correlate of immune control (26,27). These properties are interlinked and reciprocally affected by viral load, but nonetheless serve as guides to inform further studies (28)(29)(30).…”
mentioning
confidence: 99%
“…This approach incorporates numerous steps that influence virus replication in vivo, including viral entry, antigen processing, epitope presentation, epitope recognition by CD8 T cells, infected cell lysis, and subsequent spread of infection to uninfected cells. We have further demonstrated that TCR clonotypes modulate CTL function against HIV-1 infection by lytic granule loading and delivery after TCR and HLA/peptide engagement [23]. Our current data, employing the viral inhibition assay that measures the relative antiviral efficacy of multiple CTL clones specific for the same epitope from the same HIV-1 infected subject, indicate differential antiviral efficacy of CTL clones due to the distinct TCR usage and ability to produce MIP-1β.…”
Section: Introductionmentioning
confidence: 82%